FTIR spectroscopy for cancer diagnosis - Bunaciu, Andrei A. (Henry Stewart Talks, 2024)
FTIR (Fourier-transform infrared) spectroscopy and cancer diagnosis, Infrared (IR) spectra, Breast cancer and lung cancer diagnosis using FTIR spectroscopy, Characterization of epithelial ovarian cancers (EOC), FTIR and H&E imaging, Screening and follow up for childhood acute leukemia